ATP sensitive K+ channel subunits (Kir6.1, Kir6.2) are the candidate mediators regulating ameliorating effects of pulsed magnetic field on aortic contractility in diabetic rats. Issue 4 (15th February 2018) - Ocal, Isil; Yilmaz, Mehmet B.; Kocaturk‐Sel, Sabriye; Tufan, Turan; Erkoc, Mehmet A.; Comertpay, Gamze; Oksuz, Hale; Barc, Esma D.
Abstract : Diabetes mellitus is a metabolic disease that causes increased morbidity and mortality in developed and developing countries. With recent advancements in technology, alternative treatment methods have begun to be investigated in the world. This study aims to evaluate the effect of pulsed magnetic field (PMF) on vascular complications and contractile activities of aortic rings along with Kir6.1 and Kir6.2 subunit expressions of ATP‐sensitive potassium channels (KATP ) in aortas of controlled‐diabetic and non‐controlled diabetic rats. Controlled‐diabetic and non‐controlled diabetic adult male Wistar rats were exposed to PMF for a period of 6 weeks according to the PMF application protocol (1 h/day; intensity: 1.5 mT; consecutive frequency: 1, 10, 20, and 40 Hz). After PMF exposure, body weight and blood glucose levels were measured. Then, thoracic aorta tissue was extracted for relaxation–contraction and Kir6.1 and Kir6.2 expression experiments. Blood plasma glucose levels, body weight, and aortic ring contraction percentage decreased in controlled‐diabetic rats but increased in non‐controlled diabetic rats. PMF therapy repressed Kir6.1 mRNA expression in non‐controlled diabetic rats but not in controlled diabetic rats. Conversely, Kir6.2 mRNA expressions were repressed both in controlled diabetic and non‐controlled diabetic rats by PMF. Our findings suggest that the positive therapeutic effects of PMF may act through (KATP ) subunits and may frequently occur in insulin‐free conditions. Bioelectromagnetics. 39:299–311, 2018. © 2018 Wiley Periodicals, Inc.